Electricity supply in Ghana: The implications of climate-induced distortions in the water-energy equilibrium and system losses - Adom, P.K.; Agradi, M.P.; Bekoe, W. (Renewable Energy, 2019)
An important synergy exists between electricity supply security and sustainable economic development. However, distortions in the water-energy equilibrium (especially for electricity systems that heavily depend on hydropower renewable energy) and operational inefficiency in the transmission and distribution networks can affect electricity supply negatively and distort this synergy. Given the irreversible nature of capital investments and the time-dependent nature of learning abilities and information flow, it is critical to delineate the short- and long-run effects of system losses and distortions in the water-energy equilibrium on electricity availability. This study applies an econometric approach to study the case of Ghana from 1970 to 2016. Distortions in the water-energy equilibrium negatively affect electricity supply in the short- and long-run. Investment in storage renewable hydro will ensure operational flexibility and compensate for the variability in water flow. Moreover, storage hydropower is a vital asset for the development of non-flexible renewables (i.e. wind and solar) due to the synergy that exists between them. System losses have a concave effect on electricity supply, with the tolerable rate determined as 6.65%. Current levels suggest that the country should cut down on system losses by 13.35%; this requires a significant investment in transmission and distribution networks and meters.
Keywords: Electricity supply; System losses; Water-energy nexus